2019
DOI: 10.1039/c9na00405j
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale efficient water harvesting using bioinspired micro-patterned copper oxide nanoneedle surfaces and guided droplet transport

Abstract: As the Earth's atmosphere contains an abundant amount of water as vapors, a device which can capture a fraction of this water could be a cost-effective and practical way of solving the water crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 78 publications
(121 reference statements)
0
36
0
Order By: Relevance
“…For example, in our previous study, we have shown that high-density CuO nanoneedle-like morphology can be obtained by blocking the Cu layer by bisulfate ions during the oxidation process. 7 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in our previous study, we have shown that high-density CuO nanoneedle-like morphology can be obtained by blocking the Cu layer by bisulfate ions during the oxidation process. 7 …”
Section: Resultsmentioning
confidence: 99%
“…Micro/nanostructures, such as the CuO microtufts in this work, aid in the initial capture of the fog droplets from the fog stream. 7 , 48 In the case of superhydrophilic surfaces, these microstructures expand the area of the surface that encounters the fog/mist stream, which enhances the capture of the fog droplets. The wettability gradient arising from the microtufts drives the water film along the skeleton surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] However, in applications like microdrop manipulation, water harvesting, microuidic transportation, chemical/biological separation, microanalysis, and in situ detection, a sticky surface is necessary. [16][17][18][19][20][21][22] This is generally achieved using the rose petal effect, which corresponds to the Wenzel wetting state. 23 Such surfaces are fabricated by chemical etching, plasma treatment, photolithography, chemical vapor deposition, chemical coating, and using colloidal particles.…”
Section: Introductionmentioning
confidence: 99%